Endoscopic approach for cochlear implantation in advanced otosclerosis: A case report. Issue 5 (October 2016) - Marchioni, Daniele; Soloperto, Davide; Bianconi, Luca; Guarnaccia, Maria C.; Genovese, Elisabetta; Presutti, Livio
Abstract: Hypothesis: Ossification of the cochlea was once considered to be a contraindication for cochlear implantation. Advances in cochlear implant technology and coding strategies have led to developments in different surgical procedures to manage cochlear ossification. The endoscopic technique allows a direct approach to the round window and the cochlea, especially in remodeled labyrinth, allowing a better vision of scala tympani. Background: Tertiary referral ENT center. Methods: Between January 2011 and February 2015 three patients with far advanced otosclerosis with partial obliteration of the cochlea were selected and underwent endoscopic-assisted cochlear implantation. Results: In far advanced otosclerosis, endoscopy allowed a magnification of the anatomy of the round window, permitting the surrounding anatomical structures forming the anatomy of the niche to be identified, and avoiding a blind dissection. No postoperative complications were noted, in particular, no surgical site infection, no vertigo, and no facial nerve injuries. Implant activation was routinely performed 1 month after surgery. All monitoring till date has indicated that the external auditory ducts are well ventilated and there are no signs of extrusion. Conclusions: Ossification may occur as a consequence of the pathology of meningitis, chronic otitis media, severe otosclerosis, autoimmune inner ear diseases, temporal bone traumas, and other diseases. Advances in cochlear implant technology and coding strategies have led to developments in different surgical procedures to manage cochlear ossification. Supported by a number of years of experience in the field of otoendoscopic surgery, we propose a technique for cochlear implantation under unfavorable conditions using endoscopic-assisted surgery, especially in advanced otosclerosis. This technique permits us to extend the indication for cochlear implantation, and in our opinion will reduce the morbidity associated with this surgical procedure.